ANALYSIS OF ADVERTISEMENT TOOLS FOR MARKETING TOWARDS CUSTOMER BUYING BEHAVIOR FROM TELKOMSEL IN MANADO - Moromba, Yunita (Jurnal Berkala Ilmiah Efisiensi, 2015)
ABSTRACT Companies are trying to sell their products with the best advertisement, because they want to increase the number of sales. This study is conducted in Telkomsel Manado city. Telkomsel is one of the largest company of sim card for cellular phone in Indonesia. The study aims to analyze the advertisement tools for marketing towards customer buying behavior with case study Telkomsel, partially and simultaneously. Also, to determine the importance from any significant influence of television, billboards, magazines, newspaper, radio, and internet on customer buying behavior of t-sel users. This is a quantitatitive research. The method that used in this reasearch is multiple regression. 100 costumers of Telkomsel Manado were surveyed as respondents. The research comes to results is all independent variables has effected to dependent variables but the variable that mostly influence dependent variable was magazine and news paper. Â  Keywords: Advertisement Tools, Customer Buying Behaviour.